Effect of partial splenic embolization on transarterial chemoembolization for hepatocellular carcinoma with hypersplenism. Issue 26 (2nd July 2021) - Liu, Jibing; Wu, Zhijuan; Zhang, Jianxin; Xie, Yinfa; Sun, Peng; Wu, Huiyong; Chang, Xu; Zhang, Lin; Liu, Fengyong
Abstract : Abstract: This study retrospectively studied transarterial chemoembolization (TACE) combined with partial splenic embolization (PSE) in the treatment of hepatocellular carcinoma (HCC) with severe hypersplenism. Seventy patients with HCC in Barcelona Clinic Liver Cancer (BCLC) stage B or C with hypersplenism were divided into non-partial splenic embolization group (N-PSE, n = 51) and partial splenic embolization group (PSE, n = 19). The N-PSE group was further divided into N-PSE with mild to moderate hypersplenism (N-PSE-M, 47 cases) and N-PSE with severe hypersplenism (N-PSE-S, 4 cases). In the PSE group, leukocytes, neutrophils, lymphocytes, and platelets were significantly increased ( P < .05) and were significantly different from that in the N-PSE group ( P < .05). In the N-PSE group, except for a slight increase in neutrophils, other blood cells were decreased, including lymphocytes that were significantly decreased ( P < .05). There was no significant difference in the changes of liver function between the 2 groups before and after surgery ( P > .05). The analysis showed a significant increase in ascites after 6 months of TACE in the N-PSE group ( P < .05). According to the follow-up results, the median overall survival (OS) in the PSE group was 24.47 ± 3.68 (months) and progression-free survival (PFS) was 12.63 ± 4.98 (months). Regardless of OS or PFS, the PSE group was superior to the N-PSE group and its subgroups, with a statistically significant difference in PFS between the N-PSE group and PSE group ( P < .05). Moreover, the time of extrahepatic progression was significantly earlier in the N-PSE group than in the PSE group ( P < .05). N-PSE-S group had the worst prognosis, and PFS and OS were worse than the other 2 groups, suggesting that PSE in severe hypersplenism may improve PFS and OS. In patients with HCC and severe hypersplenism, TACE should be actively combined with PSE treatment.